If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(12x + -7) + -4x(15x + -11) = 30 + 29x Reorder the terms: 5x(-7 + 12x) + -4x(15x + -11) = 30 + 29x (-7 * 5x + 12x * 5x) + -4x(15x + -11) = 30 + 29x (-35x + 60x2) + -4x(15x + -11) = 30 + 29x Reorder the terms: -35x + 60x2 + -4x(-11 + 15x) = 30 + 29x -35x + 60x2 + (-11 * -4x + 15x * -4x) = 30 + 29x -35x + 60x2 + (44x + -60x2) = 30 + 29x Reorder the terms: -35x + 44x + 60x2 + -60x2 = 30 + 29x Combine like terms: -35x + 44x = 9x 9x + 60x2 + -60x2 = 30 + 29x Combine like terms: 60x2 + -60x2 = 0 9x + 0 = 30 + 29x 9x = 30 + 29x Solving 9x = 30 + 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 9x + -29x = 30 + 29x + -29x Combine like terms: 9x + -29x = -20x -20x = 30 + 29x + -29x Combine like terms: 29x + -29x = 0 -20x = 30 + 0 -20x = 30 Divide each side by '-20'. x = -1.5 Simplifying x = -1.5
| 30x=100+20x | | 3y+6x=36 | | 0.03x+0.09y=-0.27 | | 3(2f+4)=2(3-6) | | 3(5x+3)=36+6x | | -3x^2+7x+6=f(x) | | (x^3-27)(x^3-27)(x^3-27)=0 | | 5x(12x-7)-4x(15x-11)=30-29x | | -1/6(24)= | | 2/3(12)= | | 3c=2c+0 | | f(x)=-3x^2+7x+6 | | 0.15(x-4)=9.9-0.3(x-1) | | 2x+6=6x-6 | | ac+ax=b+6 | | 3=-6n+7n+18 | | 3d-14+6d+9= | | u^2=100 | | 3[a-5]=-6 | | 14+8x=-4+2x | | 4y-7+y+51=6y+50-4y | | x-1+6x=20 | | 3x+4y-7x-7y= | | 3m+(m+1)=6m+1 | | 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 | | x+y^2-2y=0 | | 10y+5x=100 | | 4y-24-9y+31= |